2021
DOI: 10.3390/ijms22084187
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Transcription Factor Binding Sites in Humans: Triggered by Natural Selection and Triggers of Diseases

Abstract: Variants of transcription factor binding sites (TFBSs) constitute an important part of the human genome. Current evidence demonstrates close links between nucleotides within TFBSs and gene expression. There are multiple pathways through which genomic sequences located in TFBSs regulate gene expression, and recent genome-wide association studies have shown the biological significance of TFBS variation in human phenotypes. However, numerous challenges remain in the study of TFBS polymorphisms. This article aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 162 publications
(228 reference statements)
0
10
0
1
Order By: Relevance
“…This is supported by the fact that nearly all (99%) accessible gene promoter regions have a SNP with most (90%) being a rare variant. Gene promoter regions are enriched for TFBSs 7 , as are accessible regions 47,48 , and thus, variation, including rare variation 49 , at TFBSs is a major target of genetic selection 50 and a key contributor to adaptive phenotypes 6,7,51 . Using TFBSs in accessible gene promoter regions, we identified a total of 3,398,768 transcription factor (TF) – target gene (TG) relationships in Nile tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the fact that nearly all (99%) accessible gene promoter regions have a SNP with most (90%) being a rare variant. Gene promoter regions are enriched for TFBSs 7 , as are accessible regions 47,48 , and thus, variation, including rare variation 49 , at TFBSs is a major target of genetic selection 50 and a key contributor to adaptive phenotypes 6,7,51 . Using TFBSs in accessible gene promoter regions, we identified a total of 3,398,768 transcription factor (TF) – target gene (TG) relationships in Nile tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the well-known risk factors such as older age, male gender, chronic active hepatitis, higher ALT levels, or history of decompensation, accumulation of genetic alteration during progression from health, through fibrosis to HCC are now considered of great importance 17 . In this study, we have focused on genetic polymorphism within transcription factor binding sites which are recently suggested as important players in downstream gene expression and phenotypic variations predisposing to different disease development 18 . We have performed an extensive literature review for candidate SNPs located at TFBSs identified by GWAS contributing to complex disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Методы полногеномного поиска ассоциаций (GWAS) позволяют идентифицировать геномные полиморфизмы, ассоциированные с различными патологиями [148][149][150][151]. Высокая частота встречаемости клинически значимых полиморфизмов в ЦРЭ позволяет предположить их влияние на регуляцию генов, задействованных в патогенезе заболевания [152]. Исследование транскриптома и GWAS-анализ позволяют предсказывать геномные локусы количественных признаков экспрессии (eQTL), ассоциированные с изменением уровня активности ОБЗОРЫ https://doi.org/10.17816/clinpract115063 генов [153].…”
Section: применение массового параллельного репортерного анализа для ...unclassified